Practical database programming with Visual Basic.NET - Bai, Ying (Hoboken, New Jersey : Wiley, 2012)
Visual Basic.NET (VB.NET) is an object-oriented computer programming language that can be viewed as an evolution of the classic Visual Basic (VB), which is implemented on the .NET Framework. Microsoft currently supplies two major implementations of Visual Basic: Microsoft Visual Studio (which is commercial software) and Microsoft Visual Studio Express (which is free of charge).
Introduction -- Introduction to databases -- Introduction to ADO.NET -- Introduction to Language Intergrated Query (LINQ) -- Data selection query with Visual Basic.NET -- Data inserting with Visual Basic.NET -- Data updating and deleting with Visual Basic.NET -- Accessing data in ASP.NET -- ASP.NET web services.
Includes index.
Keywords: MICROSOFT VISUAL BASIC